(untitled) (Bangladesh Journal of Botany, 2019)
To assess the stability of genotypes for grain yield and physio-biochemical traits associated with terminal heat tolerance pooled analysis of 8 genotypes of wheat of diverse origin, their 28 F1 progeny and 2 checks were carried out in 4 different environments i.e. early sown (E1), normal sown (E2), late sown (E3) and very late sown (E4) conditions. The pooled analysis of variance due to environment (for proline and chlorophyll content), genotypes and genotype × environment interaction was significant for all the traits under consideration. This indicated the distinct and differential effect of the different sowing conditions (environment) and differential response of all the genotypes chosen for the study. The five stable wheat hybrids viz., HI 1544 × HD 2987, Raj 4037 × HD 2987, PBW 175 × HD 2987, HD 2932 × Raj 4079 and PBW 175 × Lok 1 showed higher mean values, favourable regression coefficient and deviation from regression coefficient for grain yield and other associated characters, thus emerged as stable genotypes as per criteria of stability analysis. Similarly, some genotypes showed specific adaptations for poor or heat stress environment.